2020
DOI: 10.1177/0363546520956302
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Kaplan Fiber Injury Associated With Acute Anterior Cruciate Ligament Tear Based on Magnetic Resonance Imaging

Abstract: Background: Kaplan fibers are distinct deep layers of the distal iliotibial band (ITB) that anchor the ITB to the distal femur and have a role in rotational stability of the knee. However, the incidence of Kaplan fiber injury in the setting of acute anterior cruciate ligament (ACL) tear is unknown. Purpose: To determine the reliability of identifying and evaluating Kaplan fibers on magnetic resonance imaging (MRI) examinations based on previously reported characteristics and to report on the incidence of combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 17 publications
2
36
2
Order By: Relevance
“…Khanna et al [ 21 ] reported in a cohort of 20 patients an injury rate of 82% to the proximal- and 29% to the distal fibers, respectively. Recently, Marom et al [ 32 ] identiefied with moderate to good inter- and intrarater reliablity injuries to the Kaplan fiber complex in 51% of the examined patients. However, no clear differentiation between periligamentous edema, partial or compleate tear was made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Khanna et al [ 21 ] reported in a cohort of 20 patients an injury rate of 82% to the proximal- and 29% to the distal fibers, respectively. Recently, Marom et al [ 32 ] identiefied with moderate to good inter- and intrarater reliablity injuries to the Kaplan fiber complex in 51% of the examined patients. However, no clear differentiation between periligamentous edema, partial or compleate tear was made.…”
Section: Discussionmentioning
confidence: 99%
“… 0.94 0.94 Berthold et al [ 3 ] 2020 10 Knee specimens Proximal and distal fibers inserting distal to the lateral intermuscular septum at the metaphysis of the posterolateral femur 100% proximal fibers 90% distal fibers n.a. Excellent Excellent Marom et al [ 32 ] 2020 72 Patients with acute ACL surgery Discrete fibrous band with appropriate anatomic course and expected relationship to anatomic landmarks identified in at least 2 consecutive slices 82%/87% a 64%/71% b Proximal fibers: 0.7 Distal fibers: 0.51 Proximal fibers: 0.89 Distal fibers: 0.66 n.a. not applicable, n.s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,24 Encouragingly, independent research groups have been consistent in the radiological identification of the KFs. 1,6,22,27,30 It remains unclear, however, as to what constitutes a clinically relevant KF injury on magnetic resonance imaging (MRI) and how wide the ''goalposts'' should be set when diagnosing an injury. In the emerging literature, different rates of KF injury have been reported based on the differences in diagnostic criteria.…”
Section: Dear Editormentioning
confidence: 99%
“…8,17,25 In a recent editorial from The American Journal of Sports Medicine, the editor-in-chief, Dr Reider, stated that ''orthopaedic surgeons continue their quest for ways to increase the success rate of ACL reconstruction, the use of an adjunctive lateral extra-articular procedure is enjoying a renaissance.'' 27 Also, 38% of the members of the American Orthopaedic Society for Sports Medicine use some type of LET for selected cases. 30 Consequently, it feels that the orthopaedic society is currently divided, as considerable disagreement exists regarding the anatomic and biomechanical importance of the anterolateral complex, 13,27 and whether an LET is needed or not.…”
Section: Authors' Responsementioning
confidence: 99%